Glycaemic level and glycaemic variability in acute ischaemic stroke and functional outcome: An observational continuous glucose monitoring study - Lukana Preechasuk; Siân Rilstone; Wen Xi Tang; Jackie Man; Mingming Yang; Erica Zhao; Lily Hoque; Elif Tuncay; Peter Wilding; Ian Godsland; Omid Halse; Soma Banerjee; et al. (PLoS ONE, 2025)
Introduction Glycaemic variability has been associated with poor outcomes in critically ill patients. We aimed to study the association between glycaemic variability and functional outcome in patients with acute ischaemic stroke using continuous glucose monitoring to ensure all episodes of hyper- and hypoglycaemia were captured. Research design and methods Participants with acute ischaemic stroke were enrolled and started blinded continuous glucose monitoring (Dexcom G6) between November 2020 and December 2022. Glucose data from the first 72 hours after admission were analysed. Patients were classified into 3 groups based on change in functional status (Modified Rankin Scale) between admission and discharge. These included (i) remained independent (RI); (ii) deteriorated to dependent (DD); and (iii) remained dependent (RD). Results Data of 67 patients (mean±SD age 72.1 ± 14 years) were analysed; 19 participants had diabetes. The median (IQR) National Institutes of Health Stroke Scale (NIHSS) was 8 (3,14), and 34.3% received reperfusion therapy. The percentage of patients with RI, DD, and RD was 25.4, 55.2, 19.4%. Patients with DD had older age, higher rate of atrial fibrillation, systolic blood pressure, rate of in-hospital infection, NIHSS at admission and at 24 hours after reperfusion therapy compared to those RI. Continuous glucose monitoring was started at 38.4 (29.5,51) hours after stroke onset. Those with DD had higher mean glucose, %time above 180 mg/dL, and glucose standard deviation than the RI group at discharge. Multivariate analysis showed only an association between NIHSS at admission and deterioration in functional status. Conclusions In this pilot study, an association between glycaemic variability and functional deterioration after acute ischaemic stroke was not observed. Clinical Trial Registration numberNCT04521634